GEOCHEMICAL CHARACTERIZATION OF NICKEL MINE WATER THROUGH COLUMN LEACH TEST OF RESIDUAL ROCK AND NICKEL ORES WITH STUDY OF THE ALTERNATIVE TREATMENTS - Rossa Sandriana Naseer, Defita
Mine water characterization is crucial for understanding its behavior and environmental impact. One of the ways is to determine the geochemical characteristics of nickel mine water through kinetic column leach tests of overburden and lateritic nickel ore, which can aid in identifying alternative wastewater treatment methods for nickel mining operations. The tests carried out were physical characteristic tests, composition tests and metal content tests carried out as initial characterization, static tests, and kinetic tests along with leaching quality. The samples have a predominance of silt-sized particles with low permeability, classifying them as slow-draining. The samples exhibited porosity ranging from 0,64 to 0,70, bulk density from 1,62 to 1,68 kg/m³, and water content exceeding 50%. The results indicated that the samples could be classified as NAF and PAF with low acid generation capacity. The leachate had a likely neutral pH, with maximum TDS and TSS values of 296,94 mg/L and 131,83 mg/L, respectively. The maximum conductivity at temperature 25? and temperature was measured at 163,99 ?S/cm and 26,6?, respectively. The leachate quality tests detected total metals, dissolved as well as ions. The alternatives treatment include preventing the formation of hazardous mine water and regularly monitoring as well as managing mine water